2005
DOI: 10.1007/s00702-005-0321-5
|View full text |Cite
|
Sign up to set email alerts
|

Brain perfusion SPECT in patients with mild cognitive impairment and Alzheimer’s disease: comparison of a semiquantitative and a visual evaluation

Abstract: Due to the increasing importance of early recognition and differential diagnosis of dementias, cerebral perfusion scans using "single photon emission computed tomography" (SPECT) are increasingly integrated into the examination routine. The goal of this study was to check the diagnostic validity of SPECT scans of MCI- and DAT-patients, two subgroups out of 369 persons with etiologically unclear cognitive dysfunction, which underwent an assessment program for probable dementia including cognitive testing, crani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 38 publications
1
14
1
Order By: Relevance
“…We offer that preexisting vessel impairment (independent of vascular risk, but possibly related to AD) had to be present to potentiate the influence of vascular risk factors on vessel expandability. Opposite to earlier findings (Dai et al, 2009;Staffen et al, 2006;Hirao et al, 2005;Caroli et al, 2007), CBF was not different between NL and MCI. Global CBF was, however, related to the global cognitive abilities as assessed with MMSE.…”
Section: Vascular Risk Impairs Hippocampal Vasoreactivitycontrasting
confidence: 95%
See 1 more Smart Citation
“…We offer that preexisting vessel impairment (independent of vascular risk, but possibly related to AD) had to be present to potentiate the influence of vascular risk factors on vessel expandability. Opposite to earlier findings (Dai et al, 2009;Staffen et al, 2006;Hirao et al, 2005;Caroli et al, 2007), CBF was not different between NL and MCI. Global CBF was, however, related to the global cognitive abilities as assessed with MMSE.…”
Section: Vascular Risk Impairs Hippocampal Vasoreactivitycontrasting
confidence: 95%
“…Resting CBF reductions are also well documented by single photon emission tomography in individuals with mild cognitive impairment (MCI) (Staffen et al, 2006;Hirao et al, 2005;Caroli et al, 2007). Furthermore, both CBF reduction (Hirao et al, 2005;Caroli et al, 2007;Hansson et al, 2009;Johnson et al, 1998;Kitagawa et al, 2009;Chao et al, 2010) and deficits in the reactivity of cerebral vessels to hypercapnia (vasoreactivity to hypercapnia (VR h )) forecast cognitive decline (Silvestrini et al, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…In fact, several studies have reported rCBF decreases in the same frontal lobe location as in the current study, i.e. the superior posterior MFC [21,26,29,49,50]. In one of these studies, Caffarra et al [50] reported that all studied MCI subtypes had decreased rCBF in these regions, including individuals with dysexecutive MCI who also had the highest conversion rate to AD.…”
Section: Discussionmentioning
confidence: 88%
“…Hence, the findings in the current study differ in their locations. However, if CBF studies in early AD are examined in detail, it becomes evident that rCBF changes in many cases have also involved increases and decreases in the frontal lobe cortex [21,24,26,29,[48][49][50]. These areas have been reported as secondary findings and not highlighted as the more expected, concurrent posterior changes.…”
Section: Discussionmentioning
confidence: 99%
“…For visual ratings, as well as for parametric SPECT results, caution must be taken when interpreting the implication of an abnormal SPECT for the final diagnosis in a patient. As proposed recently in the revised research criteria [25] , SPECT (or PET) may be used as one of 3 biomarkers (diagnostic adjuncts) in the diagnosis of early AD in patients with confirmed episodic memory deficits.…”
Section: Discussionmentioning
confidence: 99%